2021
DOI: 10.46690/ager.2021.02.03
|View full text |Cite
|
Sign up to set email alerts
|

Impact of permeability heterogeneity on geothermal battery energy storage

Abstract: In the emergence of new technologies to harness renewable energy, industrial-scale storage of heated water in a geothermal system is a promising technique. A porous, permeable medium, bounded by a poorly thermally conductive/convective overburden and underburden, can be used for transient subsurface thermal storage. The reservoir in this concept forms a geothermal battery. As a very simplified scenario, consider a single well injecting and producing hot water diurnally or seasonally. The source of the hot wate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…The thickness of the reservoir affects the thermal front evolution, where the temperature will advance farther for a thinner formation. Regarding the flow rate, the thermal front will move farther for a high injection flow rate [1,2,3]. Similar studies are also performed, and the results are consistent with these findings [4,5].…”
Section: Introductionsupporting
confidence: 62%
“…The thickness of the reservoir affects the thermal front evolution, where the temperature will advance farther for a thinner formation. Regarding the flow rate, the thermal front will move farther for a high injection flow rate [1,2,3]. Similar studies are also performed, and the results are consistent with these findings [4,5].…”
Section: Introductionsupporting
confidence: 62%
“…Figure shows the geometry and meshing results of the homogeneous, weakly heterogeneous, and complex strongly heterogeneous microfluidic models. The homogeneous model was filled with a single spherical skeleton particle (1.8 μm), and the heterogeneous model was filled with spherical particles with sizes of 0.7 and 1.8 μm, , respectively. Figure gives the results of gas–water saturation distribution and interface area visualization in the homogeneous, weakly heterogeneous, and complex strongly heterogeneous models during the gas flooding process.…”
Section: Results and Discussionmentioning
confidence: 99%
“…However, horizontal and vertical permeability anisotropies in layered sedimentary rocks may lead to asymmetric temperature and pressure profiles away from a production/injection well, which needs to be considered when planning the optimal spacing between production and injection wells (Panja et al, 2021a). Numerical simulations indicate formation heterogeneity has insignificant impact on huff-puff type thermal storage system (Panja et al, 2021b). Winterleitner et al (2018) found that meter-scale heterogeneities and density-driven flow significantly influence the performance of high temperature aquifer thermal energy storage.…”
Section: Introductionmentioning
confidence: 99%